Is there a link between stress and cognition, and capacity to execute motor skill? - Serpell, B. G.; Waddington, G.; McGrath, B.; Cook, C. J. (Medicine & Science in Sports & Exercise, 2020)
Purpose: This study aimed to examine the link between stress (measured via salivary cortisol and testosterone), cognition (measured via pupillometry, with greater pupil constriction and reduced pupil constriction latency associated with increased attention and improved information processing), and motor skill capacity (measured via somatosensory processing).